Behaviour of brick-NHL render systems in presence of NaCl solution - Falchi, Laura; Speri, Laura; Balliana, Eleonora; Zuena, Martina; Zendri, Elisabetta (Ge-conservacion, 2017)
Double-layer renders were formulated for ensuring salt migration, ancient masonries conservation and environmental sustainability. Thus, natural hydraulic lime as binder and recycled aggregates from render wastes were selected. The properties were adjusted by adding an air-entraining agent in the inner layer and different percentages of water-repellent admixtures in the outer layer. The systems were applied on bricks and subjected to rising damp-evaporation cycles, for investigating their behaviour and properties in respect to NaCl migration. Mono-material prismatic render specimens were also studied. Water vapour permeability, capillary absorption, drying behaviour, compressive strength, mechanical resistance, conductivity and porosity of each formulation were evaluated. Good durability was observed whenever the render layers had different microstructure, either there was salts deposition within the lower layer,or if there was tefflorescences formation. If the layers had similar structure, deposition of salt at the brick-render interface occurred causing damages to the substrate.